2017
DOI: 10.3389/fpls.2017.01367
|View full text |Cite
|
Sign up to set email alerts
|

MhYTP1 and MhYTP2 from Apple Confer Tolerance to Multiple Abiotic Stresses in Arabidopsis thaliana

Abstract: The first YTH domain-containing RNA binding protein (YTP) was found in rat, where it was related to oxidative stress. Unlike characterizations in yeast and animals, functions of plant YTPs are less clear. Malus hupehensis (Pamp.) Rehd. YTP1 and YTP2 (MhYTP1 and MhYTP2) are known to be active in leaf senescence and fruit ripening. However, no research has been published about their roles in stress responses. Here, we investigate the stress-related functions of MhYTP1 and MhYTP2 in Arabidopsis thaliana. Both of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…The selection and creation of wheat germplasm with tolerance to multiple abiotic and biotic stresses is a key challenge for wheat breeding [ 42 56 ]. Our results and those of previous studies reveal that the expression of YTH gene is involved in the responses to various stresses and in plant development [ 10 , 13 , 15 , 17 , 21 ]. Therefore, the function of wheat YTH genes in the response to abiotic stresses merits further study, and these YTH genes might be valuable for wheat genetic improvement.…”
Section: Discussionsupporting
confidence: 84%
“…The selection and creation of wheat germplasm with tolerance to multiple abiotic and biotic stresses is a key challenge for wheat breeding [ 42 56 ]. Our results and those of previous studies reveal that the expression of YTH gene is involved in the responses to various stresses and in plant development [ 10 , 13 , 15 , 17 , 21 ]. Therefore, the function of wheat YTH genes in the response to abiotic stresses merits further study, and these YTH genes might be valuable for wheat genetic improvement.…”
Section: Discussionsupporting
confidence: 84%
“…However, there is limited direct evidence showing that YTH genes play a role in different stress responses in plants. Overexpression of MhYTP1 or MhYTP2 makes plants more sensitive to NaCl, but more resistant to nutrient deficits (Wang et al, 2017b). In addition, Wang et al (2017c) reported that, compared with wild-type plants, plants overexpressing MhYTP1 or MhYTP2 were more sensitive to heat stress and high salinity but were more resistant to waterlogging, chilling, drought, and nutrient deficiency conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Seed ethylene priming allowed the recall of long-lasting stress defensive memory, which decreased the Ethylene perception signal's gene expression. The Ethylene perception signal and root to shoot ABA secondary signal involve a dialogue between ABA, IAA, and SA, and the ABA is the dominant hormone regarding its role in plant drought tolerance (Wang et al 2017b;Zhu et al 2019;Harb et al 2020). The production of ABA in the root hair and then mobilized to the leaves will maintain plant water status through stromal regulation (Zhang et al 2018), and then postpone the development of water de cit in the aboveground (Liu et al 2005).…”
Section: Seed Ethylene Priming Recalling Long-lasting Stress Memory Tmentioning
confidence: 99%